Gender Representation in Moroccan EFL Textbooks’ Conversations: A Quantitative and Qualitative Content Analysis - BENLAGHRISSI, Hassane (International Journal of Language and Literary Studies, 2022)
By employing two analytical methods, this study investigates gender representation in the conversations of an EFL textbook currently used in Moroccan secondary schools. First, a quantitative content analysis studies the following four criteria: (1) dialogue initiation, (2) turn-taking, (3) the number of words used, and (4) the number of participants. Second, a qualitative content analysis of all the textbook conversations is carried out by examining males’ and females’ topics of the talks, their active/passive roles, their high/low status, and gender differences in language use. Although the results indicated a minor numeric difference favouring males, the qualitative analysis proved an obvious stereotypical depiction of female participants in conversations' topics by connecting them with household chores' issues and assigning them traditional gender roles. Furthermore, gender differences in language use were discovered, which confirms the results of prominent figures in the area, such as Lakoff (1975), Spender (1980), and Tannen (1991). The paper ends with a conclusion and some recommendations aiming at supporting textbooks free of sexist attitudes.